Influence of Channel Regulating Structures on the Transportation and Dissipation of Supersaturated Total Dissolved Gas. (23rd January 2021) - Qing, Yun; Ma, Qian; Li, Ran; Shen, Xia; Zhang, XuJin; Han, LinFeng
Abstract : Bubble dissolution during the flood discharge creates high total dissolved gas (TDG) concentration zones downstream of the dams. The dissipation of supersaturated TDG is a very slow process. Thus, the elevated TDG may remain through the water body for hundreds of kilometers downstream and lead to gas bubble disease (GBD) and even mortality in fish. To improve the navigation conditions of waterways, dikes (i.e., a solid structure) of varied sizes and shapes are commonly constructed. However, this would affect the dissipation and transportation of the supersaturated TDG. It would significantly change the turbulence intensity and hydropressure of the flow, which dominates the dissipation of TDG. Therefore, TDG distribution in the waterway differs from that in the natural river. In this study, a numerical simulation of the TDG at the Yangtze River's upper reaches (one of the inland waterways in China) was conducted with the establishment of a two-dimensional TDG dissipation model. The effect of the dikes' size and shape was analyzed to assess the influence of the regulation structures on the dissipation and transportation of the supersaturated TDG. Meanwhile, simulation in the study area with the natural topography was also set as blank control. Based on that, impact evaluation of TDG supersaturation on fish under different simulation scenarios was made. This study can provide a scientific basis for reducing the adverse effect of supersaturated TDG in fish and the construction of ecological waterway therefore.